Factors Influencing Fraudulent in Financial Reporting Using Fraud Triangle Theory in Malaysia: A Conceptual Paper - Mohamad Shahril Isahak; Nur Ain Hana Roslan; Nurul Syasha Izzati Abdul Tahrim; Sarah Amalin Zawari; Wan Nur Adlina Mohd Najib; Nelson Lajuni (Human Resource Management Academic Research Society, 2023)
Through the years, many highly publicised financial reporting frauds have occurred around the world. In each case, misrepresented financial reporting led to huge financial losses and a number of bankruptcies. Therefore, auditors and management are more concerned with fraud in financial reporting as it is more likely to occur, and the amounts involved are huge. This can lead to disturbing effects on the current global economy. Somehow, fraud in financial reporting can be prevented by knowing the factors that can contribute to it. Hence, with the objective of enhancing the understanding of the primary factor that caused fraudulent financial reporting, this conceptual paper aims to discuss the fraud triangle theory. In relation to this, there are three conditions that exist when fraud occurs, which are: (i) pressure, (ii) opportunity, and (iii) rationalization. In addition, this paper also aims to propose a recommendation for eliminating or minimizing the fraud triangle elements in theory.